2021
DOI: 10.3390/su13169021
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Unknown: Healthcare Workers’ Concerns, Experiences, and Burnout during the COVID-19 Pandemic—A Mixed-Methods Study in an Israeli Hospital

Abstract: The aim of this study was to describe the experiences of healthcare workers during the first wave of the coronavirus crisis. In a mixed-methods study, data were collected through an online survey completed by 263 hospital staff members, as well as 10 semi-structured, in-depth interviews with physicians, nurses, and medical technologists working on coronavirus wards. Respondents expressed extremely high levels of concern for family members, but they were less apprehensive about their own health and safety. Nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…You are the soldiers fighting a common enemy, an enemy which you don't know” ( Jones et al, 2017 ). During COVID-19, a sense of mission was similarly likened to “going to war” and … “was a job that needed to be done” ( Dopelt, Bashkin, Davidovitch, & Asna, 2021 ). HCWs reflected upon a heightened sense of role-meaning during COVID-19; it was viewed as a “vocation” ( Stoichitoiu & Baicus, 2021 ), and “…exhausting but fulfilling’( Veerapen & McKeown, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…You are the soldiers fighting a common enemy, an enemy which you don't know” ( Jones et al, 2017 ). During COVID-19, a sense of mission was similarly likened to “going to war” and … “was a job that needed to be done” ( Dopelt, Bashkin, Davidovitch, & Asna, 2021 ). HCWs reflected upon a heightened sense of role-meaning during COVID-19; it was viewed as a “vocation” ( Stoichitoiu & Baicus, 2021 ), and “…exhausting but fulfilling’( Veerapen & McKeown, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the study by Dopelt et al 16 found that a lack of recognition and appreciation led to frustration and disappointment in healthcare workers. 16 Next to support by managers, team support and bonding turned out to be important. For this purpose, people usually reverted to natural, pre-existing bonds of trust.…”
Section: Discussionmentioning
confidence: 92%
“…Results of this study showed that lack of support by the senior management severely impacted on professionals’ well-being and motivation. Similarly, the study by Dopelt et al 16 found that a lack of recognition and appreciation led to frustration and disappointment in healthcare workers 16. Next to support by managers, team support and bonding turned out to be important.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Frontline healthcare workers (HCWs) and pharmacy specialists are the ones who encounter unprecedented mental distress. The current pandemic of COVID-19 has been reported to be associated with anxiety, stress and depressive symptoms for HCWs [ 22 ]. Healthcare workers’ mental health risk and resilience factors have been addressed in recent studies, and clear communication was identified as one of the significant protective factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%